PHILOSOPHY OF RUSSIAN COSMISM. FEDOROV AND TSIOLKOVSKY: INTERSECTION OF IDEAS - O. Y. Markova; T. B. Markova (Дискурс)
The article considers how ideas of N. F. Fedorov about resuscitation and relocation of people to other planets, earthly- cosmic connections were concerned with similar considerations of K. E. Tsiolkovsky. The general development of the idea can be traced in discussions, private conversations of these persons, works and memories of Tsiolkovsky. The utopian ideas of their socio-anthropological program that have prognostic and scientific and technical basis are now relevant in environmental, moral, and economic aspects.